Marriage and Divorce under Labor Market Uncertainty - Christian Holzner; Bastian Schulz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper studies match formation and dissolution in frictional marriage markets under labor market uncertainty. We propose a search model with transferable utility in which ex-ante heterogeneous men and women simultaneously search for partners in the marriage market and switch between employment and unemployment in the labor market. In the marriage market, individuals match assortatively on education and draw a match-specific shock component representing mutual affection. Divorces can happen due to both match-specific reasons and labor market transitions, e.g. job loss of one spouse. We structurally estimate our model using German micro data and decompose the observed flow of divorces into so-called "labor market divorces" and match-specific divorces. While more than 90% of divorces happen for match-specific reasons, the share of labor market divorces has increased significantly in Germany since the mid 2000s. Interestingly, most of this increase is driven by couples in which a previously unemployed woman starts working, more so for highly-educated women. At the same time, the share of labor market divorces triggered by unemployment has decreased significantly.
Keywords: J12; J31; J64; E24; E32; 330; Search; Matching; Sorting; Marriage; Divorce; Unemployment